Pembinaan Karakter Sosial Melalui Pembelajaran Akidah Akhlak Di MTs Ishlahul Muslimin Senteluk Batulayar - Muhammad Zaini (AL-WIJDÃN Journal of Islamic Education Studies, 2019)
This study aims to find out (1) What are the social character building programs at MTs Ishlahul Muslimin Senteluk Batulayar. (2) How is the implementation of social character development programs at MTs Ishlahul Muslimin Senteluk Batulayar. Based on the location and source of the data in this research, it is included in field research, and in terms of the nature of the data, it is included in qualitative research, based on the discussion including descriptive research. Methods of data collection using observation, interviews, documentation and triangulation. Data analysis was carried out in the field, and testing the validity of the data was carried out by observation, triangulation, and peer discussion. After the researchers conducted the research, it can be concluded that social character building is necessary, 1) Creating a Social character development program needs the best possible preparation, studying it before the character building process, preparing physiologically and psychologically for the teacher. 2) In the implementation of the character development program, namely efforts to improve the social character of students, teachers use good methods / methods, namely teacher-centered and student-centered coaching using methods. Besides that, teachers must try to instill habituation and role models in all things, especially in terms of fostering social character to students in programs that have been planned. Supporting factors for character building by teachers in the implementation of social character development at MTs Ishlahul Muslimin Senteluk Batulayar include: the condition of students who have a strong level of enthusiasm and enthusiasm, stable student conditions, competent teacher conditions and willing to fight for better change, facilities and infrastructure supportive learning environment.   Keywords: Social Character, Coaching Program